Pengembangan Media Interaktif Berbasis Educandy Match-Up pada Materi Pecahan untuk Meningkatkan Numerasi Peserta Didik Kelas IV - Dyah Ayu Buana Tungga Dewi; Nurafni Nurafni (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research is motivated by the state of the class which is still carried out conventionally where the teacher uses the lecture method so that the class conditions are less active during the learning process which causes the lack of numeracy of students. From the above problems, researchers took the initiative to develop a learning media based on Educandy Match-Up to improve students' numeracy. The advantage that can be obtained from the development of this interactive media is that it creates a more active learning atmosphere so as to motivate students to be enthusiastic in learning, especially in Mathematics subjects. The purpose of this study is the existence of a decent Educandy Match-Up-based interactive media with valid and effective criteria in improving numeracy for grade IV students. This research uses ADDIE which is a model in which the stages are presented systematically. The sample was seventy-one fourth grade students from SDN Ciracas 06 and SDN Cinangka 05. Questionnaires and post-test scores from the control and experimental classes were used to collect data. The results showed that the Educandy Match-Up-based interactive media was valid with a percentage of 90.48% obtained from material experts and 95.83% obtained from media experts, the results of students' responses to learning media obtained a percentage of 82.78%, and the post-test results in the control class obtained a percentage score of 75.45% and in the experimental class obtained a percentage score of 81.48%. The development of interactive media based on Educandy Match-Up is declared valid and feasible to use to improve the numeracy of grade IV students on fraction material.